2010
DOI: 10.1186/1743-422x-7-234
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 is budded from CD4+ T lymphocytes independently of exosomes

Abstract: The convergence of HIV-1 budding and exosome biogenesis at late endosomal compartments called multivesicular bodies has fueled the debate on whether HIV-1 is budded from its target cells and transmitted in the form of exosomes. The point of contention appears to primarily derive from the types of target cells in question and lack of a well-defined protocol to separate exosomes from HIV-1. In this study, we adapted and established a simplified protocol to define the relationship between HIV-1 production and exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Although the HIV-1 preparations we used to challenge CD4 ϩ T lymphocytes were obtained by an ultracentrifugation-based procedure excluding the coprecipitation of exosomes (32), the presence of residual contaminating exosomes in HIV-1 preparations cannot be formally ruled out. However, the lack of HIV-1 infection we observed when HIV-1 was given to resting CD4 ϩ T lymphocytes alone indicated that the presence of residual exosomes contaminating our HIV-1 preparations was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Although the HIV-1 preparations we used to challenge CD4 ϩ T lymphocytes were obtained by an ultracentrifugation-based procedure excluding the coprecipitation of exosomes (32), the presence of residual contaminating exosomes in HIV-1 preparations cannot be formally ruled out. However, the lack of HIV-1 infection we observed when HIV-1 was given to resting CD4 ϩ T lymphocytes alone indicated that the presence of residual exosomes contaminating our HIV-1 preparations was negligible.…”
Section: Discussionmentioning
confidence: 99%
“…This, however, also poses a potential confound for the isolation of exosomes from HIV-1-infected materials. 34 In addition, studies on T cells and exosomes have been inconsistent and confounding. For example, some studies implicate that HIV-1 budding does not involve either endosomes or exosomes, 34, 35, 36 whereas other reports have shown that HIV-1 budding from T cells is closely associated with exosomes.…”
Section: Hiv Budding and Exosome Biogenesismentioning
confidence: 99%
“…For example, some studies implicate that HIV-1 budding does not involve either endosomes or exosomes, 34, 35, 36 whereas other reports have shown that HIV-1 budding from T cells is closely associated with exosomes. 37 In this regard, Park and He 34 have shown that high-speed centrifugation with 20% sucrose cushion during the last step can yield exosome-free HIV-1 virions compared with centrifugation only. Herein the authors provided a technical platform that could be employed to define the relationship between exosome biogenesis and budding of HIV-1.…”
Section: Hiv Budding and Exosome Biogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, HIV recruits members of the MVB ESCRT complex for proper HIV budding from the plasma membrane [98][99][100][101][102]. While in CD4+ T cells HIV release appears to be independent of exosomes [103], in monocyte-derived macrophages HIV can bud into endosomes [102,104]. However, several studies highlight that HIV-1 budding also in macrophages occurs primary at the plasma membrane [105][106][107].…”
Section: Hiv and Microvesiclesmentioning
confidence: 99%